Het Leven : geïllustreerd. (Amsterdam, 1914)
Bibliotheek Camille Huysmans
Periodiciteit: wekelijks
Hoofdredactie: Frans Van Erlevoordt
Beheer/Administratie: Keizersgracht 268, Amsterdam
Drukker/Drukkerij: Holdert & Co, Amsterdam
Nederlands
Periodiek